2009
DOI: 10.1177/0192623308327119
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protease Inhibitors in the Pathogenesis of HIV-Associated Lipodystrophy: Cellular Mechanisms and Clinical Implications

Abstract: Metabolic complications associated with HIV infection and treatment frequently present as a relative lack of peripheral adipose tissue associated with dyslipidemia and insulin resistance. In this review we explain the connection between abnormalities of intermediary metabolism, observed either in vitro or in vivo, and this group of metabolic effects. We review molecular mechanisms by which the HIV protease inhibitor (PI) class of drugs may affect the normal stimulatory effect of insulin on glucose and fat stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 121 publications
(189 reference statements)
1
56
0
1
Order By: Relevance
“…PIs may cause lipodystrophy by inhibiting ZMPSTE24, resulting in accumulation of toxic farnesylated prelamin A [128], increased oxidative stress and altered adipokine and cytokine production [89,127,129]. The adverse effect of PIs could also result from the induction of endoplasmic reticulum stress or the inhibition of the proteasome [130,131]. Different PIs might affect key intranuclear genes, causing reduction in levels of RNA encoding SREBP-1, which changes the expression of PPAR γ [28].…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…PIs may cause lipodystrophy by inhibiting ZMPSTE24, resulting in accumulation of toxic farnesylated prelamin A [128], increased oxidative stress and altered adipokine and cytokine production [89,127,129]. The adverse effect of PIs could also result from the induction of endoplasmic reticulum stress or the inhibition of the proteasome [130,131]. Different PIs might affect key intranuclear genes, causing reduction in levels of RNA encoding SREBP-1, which changes the expression of PPAR γ [28].…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…3 Specifically, some ritonavirboosted PIs have been associated with a worsening of lipid parameters and increases in inflammatory markers. [4][5][6][7] Additionally, some PIs have been associated with insulin resistance in HIV-negative healthy volunteers. [8][9][10][11] However, this association with insulin resistance seems to be ARV-specific, as opposed to class-specific, as studies evaluating other PIs have failed to demonstrate such an association.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that PIs directly block glucose uptake though suppressing glucose transporter protein isoform 4 (GLUT4, SLC2A4) activity leading to reduced glucose uptake and hyperglycemia [10,22,23,29]. These effects appear to be caused by suppression of GLUT4 transport function and not translocation or interference with insulin signalling cascade [30].…”
Section: Pi-induced Glucose Intolerance and Insulin Resistancementioning
confidence: 99%